Examination of elementary students' emotions and personal and social responsibility in physical education. (November 2021) - Simonton, Kelly L.; Shiver, Victoria N.
This study examined the relationships between student emotions in elementary physical education (PE) and their self-reported personal and social behaviors. Additionally, self-reported emotion and personal and social behavior differences were tested between students receiving a traditional multiactivity and games PE curriculum and those experiencing a Teaching Personal and Social Responsibility (TPSR) model curriculum. Participants were 2nd and 3rd grade students ( n =222) from two schools in the United States. Both schools had similar student demographics, school needs, and community characteristics. For secondary comparison analysis, school one ( n =87) served as the comparative school receiving a traditional multiactivity curriculum and school two ( n =135) received the TPSR model. Results showed that enjoyment and anger were predictors of students' behavioral engagement. Findings also disclosed a significant positive effect for enjoyment, perceived responsibility, and behavioral engagement favoring the TPSR group. The TPSR model may be positively associated with elementary students' beliefs about responsible behaviors, student enjoyment, and training students in positive ways to deal with anger. Overall, investigating the relationship between students' emotions and their personal and social development, as it relates to PE, may provide intervention to reduce some negative experiences students report in these environments. Likewise, positive emotional experiences may increase in-class engagement and the adoption of adaptive personal and social responsibilities within PE and potentially into other areas in and out of school.